2018
DOI: 10.1007/s11906-018-0824-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of Energy Expenditure by AgRP Neurons of the Arcuate Nucleus: Neurocircuitry, Signaling Pathways, and Angiotensin

Abstract: The development and maintenance of obesity involves suppression of resting metabolic rate (RMR). RMR control is integrated via AgRP and proopiomelanocortin neurons within the ARC. Their projections to other hypothalamic and extrahypothalamic nuclei contribute to RMR control, though relatively little is known about the contributions of individual projections and the neurotransmitters involved. Recent studies highlight a role for AT, localized to AgRP neurons, but the specific function of AT within these cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 74 publications
3
20
0
Order By: Relevance
“…Among them, hypothalamic ARC, attached to the bottom of the third ventricle, is of crucial importance to integration of peripheral metabolic signals on energy status [ 10 ]. Recent research shows that distinct neuronal populations in hypothalamic ARC, such as proopiomelanocortin (POMC) neurons and agouti-related protein (AgRP) neurons, regulate BAT thermogenesis via activation of sympathetic nervous system [ 11 ]. These neurons project mainly to second-order neurons in the hypothalamic DMN and PVN, leading to an integrated response on BAT thermogenesis and energy expenditure [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, hypothalamic ARC, attached to the bottom of the third ventricle, is of crucial importance to integration of peripheral metabolic signals on energy status [ 10 ]. Recent research shows that distinct neuronal populations in hypothalamic ARC, such as proopiomelanocortin (POMC) neurons and agouti-related protein (AgRP) neurons, regulate BAT thermogenesis via activation of sympathetic nervous system [ 11 ]. These neurons project mainly to second-order neurons in the hypothalamic DMN and PVN, leading to an integrated response on BAT thermogenesis and energy expenditure [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that asip can affect melanocyte differentiation and maturation in mice [ 49 ]. Meanwhile, mammalian agrp is mainly expressed in the hypothalamus where it has predominantly been explored in the context of regulating energy balance [ 50 , 51 ]. In contrast to tetrapods, teleosts have four endogenous antagonists: asip1, asip2, agrp1 and agrp2 due to genome duplication [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided evidence that AgRP was only synthesized in NPYcontaining cell bodies that were located in the ventromedial part of the arcuate nucleus in the hypothalamus. 25 The AgRP is an effective peptide that promotes appetite, and the appetite-stimulating effect of AgRP was activated by the hormone ghrelin, which further increased food intake when AgRP was overexpressed. 26 Similarly, Zhang et al 27 also showed that AgRP was closely associated with glucose homeostasis and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%